Speeches and practices of the rural development: a reading from caldas department, colombia (2011)
To contribute to the current debate on rurality, research was conducted focusing on the discourses and practices of rural development. To this end, documents were reviewed that address this topic from 1950 to 2007, and was examined primary information provided by officials from various institutions and programs oriented rural development projects in Caldas. It was found a predominance of economic and productive approaches in rural development practices, and an eclectic position in speeches. Analysis of primary sources can be inferred that in Caldas there is a vanguard and theoretical management of the concept, but the practices continue to be guided by principles derived from theories and models considered outdated.